DESIGNING ECONOMICALLY SUSTAINABLE FAMILY FARMS: INTEGRATING CIRCULAR ECONOMY AND PERMACULTURE FOR RESILIENT AGRICULTURAL PRACTICES - Besiana Hoxha (Journal of Bio-Based Marketing)
Sustainability was first defined by Hans Carl von Carlowitz, and it is understood as the ability to meet our current needs without compromising the ability of future generations to meet their own needs. The process of sustainable development involves the interaction of biological, social, and economic systems, aiming to maximize their goals, which include, among others, genetic diversity, fulfilling basic human needs, and cultural diversity. The concept of a circular economy supports sustainable development, as it is based on designing systems, elements, processes, products, and services in such a way that waste, which is currently a major ecological and social problem, does not exist. This economic development, which emphasizes the preservation of natural resources (essential for human survival) rather than profit, represents the only viable future perspective that does not appear apocalyptic. Sustainable family farms are often based on permaculture principles. This primarily means avoiding chemical and mineral additives, as well as heavy machinery, but also requires designing systems that create multiple functional links between various elements within the farm, as well as between the farm and natural energy flows. The paper describes the main prerequisites that a family farm must meet in order to be considered sustainable, as well as ways to organize similar farms into cooperatives and eco-villages based on cooperative principles.